GERAKAN PENUMBUHAN BUDI PEKERTI SISWA SEKOLAH DASAR MENGGUNAKAN PERANGKAT MOBILE: GERAKAN PENUMBUHAN BUDI PEKERTI SISWA SEKOLAH DASAR MENGGUNAKAN PERANGKAT MOBILE - Winarni, Endang Widi (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2018)
The purpose of this activity is to improve the capacity of elementary school teachers on the student movement movement program using mobile learning, the ability and skills of teachers in designing, implementing and evaluating the program of student's character growth movement and improving students' positive response about the movement of character development program. This activity is carried out through observation and modeling with four phases, namely: the phase of attention (attential phase), retention phase (retention phase), reproduction phase (reproduction phase), and motivation phase (motivation phase). The results show that there is an increase in teacher understanding about the assessment of students' character growth programs through mobile learning.